Actual Aspects of Epidemiological Well-Being Support Anti-PLAgue for Population in Altai Republic - S. V. Balakhonov; V. M. Korzun; S. A. Kosilko; E. P. Mikhailov; L. V. Shchuchinov; A. I. Mishchenko; I. V. Zarubin; E. N. Rozhdestvensky; A. V. Denisov (Эпидемиология и вакцинопрофилактика, 2016)
Relevance. Despite significant advances in modern medicine in the treatment of infectious diseases, the plague has not lost its relevance and is one of the socially significant epidemic threats as a particularly dangerous infection. Every year, there are nearly 2.5 thousand cases of plague in the world, and the mortality rate 7 - 13%. Goal. Analysis of the current epizootic and epidemiological situation of the plague, and to determine the optimal set of preventive measures to ensure epidemiological welfare of population of the Republic of Altai on this particularly dangerous infectious disease. Materials and methods. Used the results of monitoring in 1961 - 2015 years of Gorno-Altai natural foci of plague. For more than 50 years bacteriologically were examined more than 290 thousand. small mammals, more than 1545 thousand fleas, isolated 2435 strains of the plague pathogen. Results. In recent years, the Gorno-Altai foci of plague most active of the 11 natural focis, located in Russia. On the Gorno-Altai territory in 2001 to 2014 isolated 801 strain of the pathogen, in 2015 - 23 strains, including 17 main subspecies. currently in the Gorno-Altai natural foci of plague there is a joint circulation of the two subspecies of the plague microbe: Y. pestis subsp. altaica and Y. pestis subsp. pestis. In September 2014 the first time since the detection foci of plague (1961) recorded the local human case of bubonic plague. in August 2015 identified a new case of the plague Conclusions. Introduction of the plague pathogen main subspecies into the ecosystem of the Gorno-Altaisk natural foci of plague greatly increases the possibility of dangerous epidemiological situation